Effect of Environmental Responsibility on Financial Performance: Organization Slack as Moderation - Cahyaningsih Cahyaningsih; Dieni Maitsa Nuralifah (AFRE (Accounting and Financial Review), 2024)
This study analyze the effect of environmental responsibility on financial performance with organization slack as a moderating variable. This study examines 21 property and real estate sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Data analysis used panel data regression with the results of the random effect model. The result shows that environmental responsibility positively affects financial performance. Companies that implement environmental responsibility can avoid conflicts or losses that can disrupt company activities so that financial performance is increasing. The fin-ding presents that organization slack positively affects financial performance. Excess resources can be used to increase investment so that financial performance also increases. Moderation testing proves that organization slack strengthens the positive influence of environmental responsibility on financial performance. Excess resources provide opportunities for companies to invest in the social sector and meet stakeholders' demands and expectations. JEL Classification: G32; Q56; M14; L25 DOI: https://doi.org/10.26905/afr.v7i3.10931